The stained glass window : a family history as the American story, 1790-1958 - Lewis, David Levering, 1936- (Penguin Press, 2025)
"National Humanities Medal recipient and two-time recipient of the Pulitzer Prize David Levering Lewis's own family history that shifts our understanding of the larger American story. Sitting beneath a stained-glass window dedicated to his grandmother in the Atlanta church where his family had prayed for generations, it struck Lewis that he knew very little about those ancestors. And so, in his mid-80s, the esteemed historian began to excavate their past and his own. We know that there is no singular, quintessential American story. Yet, the Lewis family contains many defining ones. His lineage leads him to the Kings and Belvinses, two white slaveholding families in Georgia; to the Bells, a mulatto slaveholding family in South Carolina; and to the Lewises, an up-from-slavery black family in Georgia. In The Stained-Glass Window, Lewis is heir and chronicler of them all. His father, John Henry Lewis, Sr. set Lewis on the path he would doggedly pursue, introducing him to W.E.B. Du Bois and living by example as an aid to Thurgood Marshall in a key civil rights case in Little Rock. In The Stained-Glass Widow, Lewis reckons with his legacy in full, facing his ancestors and all that was lost, all the doors that were closed to them. In this country, the bonds of kinship and the horrific fetters of slavery are themselves bound up together. The fight for equity, the loud echoes of the antebellum project in our present, and narratives of exceptionalism are ever with us-in these pages, so too are the voices of Clarissa, Isaac, Hattie, Alice, and John who have shaped this nation and will transform the way we see it"--